ttcrpy: A Python package for traveltime computation and raytracing - Giroux, Bernard (SoftwareX, 2021)
ttcrpy is a package for computing traveltimes and raytracing of seismic and electromagnetic waves for geophysical applications, e.g. ray-based seismic/GPR tomography, microseismic event location (joint hypocenter-velocity inversion), and migration. The package allows performing computations on 2D and 3D rectilinear grids, as well as 2D triangular and 3D tetrahedral meshes. For improved versatility, three different algorithms have been implemented: the Fast-Sweeping Method, the Shortest-Path Method, and the Dynamic Shortest-Path Method. Calculations can be run in parallel on a multi-core machine. The core computing code is written in C＋＋, and has been wrapped with Cython for practical use.